Epidemiology of colorectal cancer in the world - the Arab world and Algeria in particular - Soufiane , cheheb; Saidoun, Djahid (Al-Jamie Journal In Psychological Studies and Educational Sciences, 2025)
This research aims to highlight the epidemiology of colorectal cancer, by addressing the factors of infection and prevention, and to determine the extent of the alarming development and spread of this disease in Algeria, in some Arab countries, and in the world in recent years, and to highlight the differences in infection between the sexes, This was achieved by relying on data from the World Health Organization, in addition to presenting national statistics based on various national networks of tumor registries. To achieve the research objectives, we used the descriptive exploratory approach to gain a comprehensive understanding of the phenomenon under study. Through this research, we have concluded that colon and rectal cancer is one of the most common cancers in the world, in the Arab world, and in Algeria, occupying very high ranks. It affects both males and females without exception, with some differences recorded in terms of the severity of its spread, both at the level of geographical distribution and at the level of gender. Globally, Europe is the continent most affected by this disease. On the Arab level, the Kingdom of Saudi Arabia is witnessing a widespread outbreak. Males are more affected than females. The disease is also more prevalent in developed countries with a high standard of living. The study concluded with a set of recommendations, including: - Instilling a culture of early detection of this disease to limit its spread. - Following a healthy diet that includes a significant number of whole fruits and vegetables. - Moderating consumption of red meat and avoiding canned, processed, and frozen meats. - Regular exercise to maintain a healthy body weight. - The need to strengthen health services and provide healthcare facilities specializing in cancer treatment with qualified medical personnel and equipment.